2000
DOI: 10.1177/000331970005101002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angioplasty and Stenting in Orthotopic Heart Transplants: A Fruitful Act or a Futile Attempt?

Abstract: Accelerated allograft coronary artery disease remains the major cause of mortality after the first year of transplantation. Despite the extensive use of stents and angioplasty in coronary artery disease, there is a paucity of data about the efficacy of such interventions in orthotopic heart transplants. The authors herein report the outcome of those patients in their institution who had undergone percutaneous coronary artery angioplasty and stenting at a late stage of their transplantation. Within a 12-year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…Our analysis is in concert with available studies in heart transplant recipients examining the benefit of PTCA with stenting in which restenosis rates at 6 to 12 months are consistently lower with the addition of stents (10,15,16). We found a significant reduction in the freedom from restenosis both early and late after PTCA with nearly a 50% reduction in restenosis at eight months.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our analysis is in concert with available studies in heart transplant recipients examining the benefit of PTCA with stenting in which restenosis rates at 6 to 12 months are consistently lower with the addition of stents (10,15,16). We found a significant reduction in the freedom from restenosis both early and late after PTCA with nearly a 50% reduction in restenosis at eight months.…”
Section: Discussionsupporting
confidence: 64%
“…In several smaller studies of cardiac transplant recipients undergoing PCIs, a cumulative of 83 patients underwent PTCA without stenting and Benza et al June 2, 2004June 2, :1973 PTCA and Allograft Vasculopathy demonstrated restenosis rates of 14% to 61% at four to seven months (7)(8)(9)(12)(13)(14) In addition, one multicenter study of 35 patients undergoing PTCA of 95 lesions demonstrated a 55% restenosis rate at seven months. In several later studies in patients undergoing PTCA alone, the restenosis rate at two to six months ranged from 67% to 100% (10,15,16). Unfortunately, in many of these studies, the definitions for restenosis and the duration of follow-up differed, resulting in considerable variability in the restenosis rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, the procedure was associated with 2 major complications (1 death) and a restenosis rate of 82%. Although this is a small series, these results are consid- 1,4,7,8 This may be due in part to their smaller vessels and by necessity the use of smaller stents. In this study, the maximum balloon diameter ranged from 2.0 to 3.25 mm (median, 2.5 mm), and the maximum stent diameter ranged from 2.5 to 3.0 mm (median, 2.75 mm).…”
Section: Discussionmentioning
confidence: 81%
“…[14][15][16] Once clinically significant CAV is apparent, percutaneous coronary intervention (PCI) is successful for focal disease, although restenosis is common in the transplant setting. 55 Drug-eluting stents may help, but restenosis rates continue to be higher than for similar interventions in the nontransplant population. 56,57 There is no evidence to date that PCI alters the prognosis of CAV and, because many patients with significant disease are asymptomatic, intervention often presents a dilemma.…”
Section: Treatment Of Cardiac Allograft Vasculopathymentioning
confidence: 99%